Implementasi Environmental Graphic Design untuk Penguatan Identitas Visual dan Navigasi Desa Wisata - Stefvany, Stefvany; Wiraseptya, Tedy; Suryadi, Dodi (Jurnal Pengabdian UNDIKMA, 2025)
This community service program aims to strengthen the visual identity and navigation system of a tourism village through the application of Environmental Graphic Design (EGD) while simultaneously enhancing the local community’s skills in managing digital promotion. The implementation method adopted a community-based participatory approach consisting of five stages: socialization, training, technology implementation, mentoring, and continuous evaluation. Evaluation was conducted using field observation instruments, structured interviews, and visitor satisfaction questionnaires. The data were analyzed descriptively, both quantitatively and qualitatively, to assess the effectiveness of the design and the improvement of partner capacity. The outcomes of this community service program include the installation of seven thematic signage units, one interactive digital tourism map, and one identity mural, as well as the improvement of the tourism awareness group’s (Pokdarwis) skills in environmental graphic design and digital promotional content management. The implementation of EGD has proven effective in strengthening the visual image of the destination, improving visitor comfort and orientation, and promoting the sustainable growth of village-based creative economies.